BRAND AMBASSADOR AND PRODUCT QUALITY INFLUENCE CONSUMER BUYING INTEREST - Faritzal, Adam; Avrillia, Avrillia; Padmakusumah, Rizal Ramdan; Dwiyogo, Santos Winarso; Nurunnisha, Gina Apryani (ITB AAS Indonesia Surakarta, 2024)
The beauty industry is one of the most demanded industries by all people at this time both in Indonesia and internationally, this is due to the increasing awareness of self-care and self-beautification so that it has become a necessity and has become a lifestyle of today's modern society. .The purpose of this study is to find out how the influence of Brand Ambassador, product quality on buying interest in Nature Republic, either partially or simultaneously. The method used is descriptive and verification.The population in this study were residents of the city of Bandung, while the sampling technique used by researchers was using a purposive sampling technique, namely selecting samples based on certain criteria so that they were used in research with a sample size of 100 respondents. The results of the study show that brand ambassadors are good enough that they need to be improved again. Even though the respondents' responses regarding product quality were quite good, there was still a low rating that needed to be improved. Likewise, the buying interest in Nature Republic, based on the respondents' responses, is considered high, although there is still a low rating and needs to be improved